The tonology of Xhosa - Claughton, John Sellick (Rhodes University, Faculty of Humanities, School of Languages, 1992)
This thesis is an examination of the tonology of Xhosa. After an initial survey of the surface tones of the language, and a review of previous studies of Xhosa tone, a description is given of the major tonal patterns of Xhosa noun and verb morphology. In the course of this description the major tonologica1 rules are allowed to emerge. In particular it is shown that some of these rules lead to complex patterns of variation in the pronunciation of the same individual. The derivation of the tone patterns of adjectives and relatives is discussed and it is shown that these tone patterns offer partial support for the derivation of some adjective and relative constructions as derived from embedded sentences but also support for deriving simple attributive adjective constructions by means of phrase structure rules. Some interesting tonal patterns such as that shown by reduplicated stems are then explored. The tones of loan words are then investigated and evidence for the identification of English and Afrikaans stress with high tones by Xhosa speakers is adduced. In the final chapter certain general problems of Xhosa tone are discussed. In particular it is argued that attempts to interpret the tonal system in terms of an accent are unrevealing and also it is suggested that attempts to unify the various rules that spread tones to the right are mistaken. In the appendices a comprehensive survey of the tones of Xhosa inflections is given together with a substantial list of Xhosa words with the tones marked.
Keywords: Xhosa language -- Tone